Exogenous fatty acid binding protein 4 promotes human prostate cancer cell progression. Issue 11 (23rd April 2014) - Uehara, Hisanori; Takahashi, Tetsuyuki; Oha, Mina; Ogawa, Hirohisa; Izumi, Keisuke
<x xml:space="preserve">Abstract</x> Epidemiologic studies have found that obesity is associated with malignant grade and mortality in prostate cancer. Several adipokines have been implicated as putative mediating factors between obesity and prostate cancer. Fatty acid binding protein 4 (FABP4), a member of the cytoplasmic fatty acid binding protein multigene family, was recently identified as a novel adipokine. Although FABP4 is released from adipocytes and mean circulating concentrations of FABP4 are linked with obesity, effects of exogenous FABP4 on prostate cancer progression are unclear. In this study, we examined the effects of exogenous FABP4 on human prostate cancer cell progression. FABP4 treatment promoted serum‐induced prostate cancer cell invasion in vitro. Furthermore, oleic acid promoted prostate cancer cell invasion only if FABP4 was present in the medium. These promoting effects were reduced by FABP4 inhibitor, which inhibits FABP4 binding to fatty acids. Immunostaining for FABP4 showed that exogenous FABP4 was taken up into DU145 cells in three‐dimensional culture. In mice, treatment with FABP4 inhibitor reduced the subcutaneous growth and lung metastasis of prostate cancer cells. Immunohistochemical analysis showed that the number of apoptotic cells, positive for cleaved caspase‐3 and cleaved PARP, was increased in subcutaneous tumors of FABP4 inhibitor‐treated mice, as compared with control mice. These results suggest that exogenous FABP4 might promote human prostate cancer cell progression by binding with fatty acids. Additionally, exogenous FABP4 activated the PI3K/Akt pathway, independently of binding to fatty acids. Thus, FABP4 might be a key molecule to understand the mechanisms underlying the obesity‐prostate cancer progression link.